Significance and role of the microbiome for skin health - Todorović, Jelena (Archives of Pharmacy, 2022)
Healthy human skin in its epidermal and dermal layers is colonized by a diverse population of microorganisms that we call microflora (microbiota) of the skin. Microbiome is a term that refers to the genetic material of all microorganisms that live on and inside the human body, have their own purpose and style of protection of the human body, and can be seen as a key component in the function of the skin as a barrier against threats and infections from the environment. When looking at the role of the microbiome in maintaining skin health, it is first important to understand that this is a two-way dynamic relationship - healthy skin is necessary to maintain a healthy microbiome, and a balanced skin microbiome also contributes and helps maintain the skin barrier, as well as maintaining a healthy and stable skin environment. However, if the composition of the normal skin microbiome is disrupted, inflammation, irritation, dryness, itching and deterioration of the skin can occur, challenging our immune system, leading to inflammatory conditions such as acne, atopic dermatitis and psoriasis. The interrelationship between microbial communities and us as hosts is essential to health, gaining better insight into the pathophysiological aspects of skin diseases and helping to develop age-appropriate treatments, as well as the development of cosmetic products, which involves one of three basic approaches, which is an attempt to balance or improving the skin microbiome, protecting the skin microbiome, and activating the microbiome to achieve different effects on the skin.